mi-RNA129-1 and mi-RNA24-2 as regulators of over-expressed genes in lung typical carcinoid tumors: Potential targets for molecular therapy - Abbas Chakhtoura, Jad (2023)
Lung carcinoid tumors are malignant neuroendocrine neoplasms that account for less than 2% of all lung malignancies and include two histological types: typical and atypical carcinoid tumors. Typical carcinoid tumors do not include areas of necrosis and show less than 2 mitotic figures within 10 high grade fields. On the molecular level, carcinoid tumors present alterations in gene MEN1 as well as a high expression of genes ASCL1 and EIF1AX. We report a systems biology approach using BioNetUCR and Copasi in addition to Cytoscape to identify mi-RNA regulators of the most important altered genes in typical pulmonary carcinoid tumors. The final adjusted and reduced interaction network of our genes of interest included: 3 genes 12 transcription factors and 7 mi-RNAs, leading to a total of 22 nodes and 53 edges. Analysis with Copasi showed that MIR24-2 regulates the expression of MEN1 and MIR129-1 regulates the expression of AIF1AX. Those mi-RNAs could be potential targets for molecular therapy in patients with typical carcinoid tumor of lung.